Analysis of the role of BrRPP1 gene in Chinese cabbage infected by Plasmodiophora brassicae - Ge, Wenjie; Lv, Mingcan; Feng, Hui; Wang, Xinlei; Zhang, Bo; Li, Ken; Zhang, Jing; Zou, Jiawei; Ji, Ruiqin (Frontiers in Plant Science, 2023)
The clubroot disease caused by Plasmodiophora brassicae (P. brassicae) poses a serious threat to the economic value of cruciferous crops, which is a serious problem to be solved worldwide. Some resistance genes to clubroot disease in Brassica rapa L. ssp pekinensis cause by P. brassicae have been located on different chromosomes. Among them, Rcr1 and Rcr2 were mapped to the common candidate gene Bra019410, but its resistance mechanism is not clear yet. In this experiment, we found that the sequence of Bra019410 is homologous to the Arabidopsis AT5G11250 (Recognition of Peronospora parasitica1, RPP1), so it was named as BrRPP1. The cDNA sequence, upstream promoter sequence and expression level of BrRPP1 were quite different between the resistant and susceptible material of Chinese cabbage. The resistance investigation found that the Arabidopsis mutant rpp1 was more susceptible to clubroot disease than the wild type, which suggested that the deletion of rpp1 reduces resistance of plant to clubroot disease. Subcellular location analysis confirmed that BrRPP1 was located in the nucleus. The interaction proteins of BrRPP1 screened from cDNA Yeast Library by yeast two-hybrid are mainly related to photosynthesis, cell wall modification, jasmonic acid signal transduction and programmed cell death. These results provide important clues for understanding the mechanism of BrRPP1 in the resistance of B. rapa to P. brassicae.